The Future of Cryptocurrencies: Revolutionizing the Financial Landscape - Raju, Robin (European Journal of Applied Sciences, 2024)
This research explores the impact of cryptocurrencies on the financial landscape, focusing on the rise of blockchain technology, the emergence of central bank digital currencies (CBDCs), and the growth of decentralized finance (DeFi). The study examines the regulatory environment of cryptocurrencies in Australia and the challenges and opportunities associated with their adoption. Key findings highlight the transformative potential of cryptocurrencies in revolutionizing traditional financial systems by increasing transparency, efficiency, and accessibility. The research emphasizes the importance of adapting policies to support the evolving cryptocurrency market.